2019
DOI: 10.26694/2358.1735.2019.v6ed17682
|View full text |Cite
|
Sign up to set email alerts
|

Regime Aduaneiro Especial De Drawback Como Redutor De Custos No Setor De Fruticultura

Abstract: Como a prática do comercio exterior vem se fortalecendo ao passar dos anos, já que a mesma se tornou de fundamental relevância para o crescimento econômico dos países, torna-se necessário que as empresas tenham conhecimento e estejam preparadas para competir com os diversos tipos de mercado no âmbito internacional. Nos processos de importação não é diferente, uma vez que a alta carga tributária brasileira impede que esse processo seja praticável sem que haja algum incentivo que possa minimizar os custos. Dessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
1
0
2
Order By: Relevance
“…Grassmann & de Moura (2018), in the import of inputs destined for the production of finished textile products for export, obtained a reduction in the cost of nationalization of inputs of up to 14%, values well below that found in this study. However, Almeida et al (2019) in the fruit sector found using the special customs regime of Drawback as a cost reducer, 31,63%, a result very close to that found in this study. Such a system is not very bureaucratic and can be implemented in a simple way, including in timber companies.…”
Section: Comparison Of Values Before and After The Drawback Regimesupporting
confidence: 88%
See 1 more Smart Citation
“…Grassmann & de Moura (2018), in the import of inputs destined for the production of finished textile products for export, obtained a reduction in the cost of nationalization of inputs of up to 14%, values well below that found in this study. However, Almeida et al (2019) in the fruit sector found using the special customs regime of Drawback as a cost reducer, 31,63%, a result very close to that found in this study. Such a system is not very bureaucratic and can be implemented in a simple way, including in timber companies.…”
Section: Comparison Of Values Before and After The Drawback Regimesupporting
confidence: 88%
“…In several studies, Grassmann & de Moura (2018), Almeida et al (2019); Pedroza Filho & Rocha (2019), Floriano et al (2020), Pereira et al (2020), Takano et al (2021) using the integrated Drawback system achieved a reduction in the costs of inputs used in the export of products, generating significant savings in production costs and increasing their competitiveness in the market. The Brazilian forestry market is characterized by exporting products with low added value, mainly sawn wood and cellulose (Andrade, 2014).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Dentre os diferentes regimes de tributação e a dificuldade de internacionalização, o governo brasileiro instituiu um regime aduaneiro especial de tributação, o Drawback, que é um incentivo à exportação da produção de empresas brasileiras (Brasil, 1966). Esse regime é capaz de desonerar os exportadores sob o aspecto financeiro, concedendo suspensão, isenção ou restituição de tributos aos importadores e exportadores, podendo ser considerado um incentivo financeiro (Pirett, Pirett & Cezarino, 2019;Ameida et al, 2018).…”
Section: Introductionunclassified
“…Quanto aos aspectos práticos, a pesquisa traz contribuições para a tomada de decisão no frigorífico pesquisado, bem como, servir de base para demais entidades que perpassam por situação semelhante, vislumbrando no Drawback uma alternativa. Ademais diferentes estudos como o dos autores Santos, Cardoso e Toledo e Filho (2004); Olivo e Zilli (2014); Fabris (2017); Ameida et al (2018); Bart e Dörr (2017) desde que, vinculadas a um compromisso de exportação (MDIC, 2013). Ao longo do tempo, as modificações na legislação, bem como o aperfeiçoamento das tecnologias de informação e comunicação, possibilitaram a evolução do regime até chegar no modelo atual de Drawback integrado que, permite também, a desoneração de tributos na aquisição de insumos no mercado interno (MDIC, 2013).…”
Section: Introductionunclassified